Method Development and Clinical Utility for Simultaneous Measurement of 21-Deoxycortisol, 17-Hydroxyprogesterone, Cortisol, and Cortisone Levels in Human Plasma Using UHPLC-MS/MS - Syed N. Alvi; Saleh Al dgither; Ali Al-Odaib (Advances in Pharmacological and Pharmaceutical Sciences)
A simple and efficient validated assay for quantifying 21-deoxycortisol (21-DOC), 17-hydroxyprogesterone (17-OHP), cortisol, and cortisone in human plasma has been developed using ultra-high performance liquid chromatography coupled with tandem mass spectrometry (UHPLC-MS/MS). Analysis of plasma samples were performed on Atlantis dC18 (3 μm) column using a mobile phase of 20.0 mM ammonium acetate and acetonitrile (50:50, v:v) that was delivered at isocratic flow rate 0.3 mL/minute. After addition of d4-cortisol as an internal standard (IS), plasma samples containing 21-DOC, 17-OHP, cortisol, and cortisone were extracted with mixture of dichloromethane and tert-butylmethyl ether 1:2 (v/v). Analytes were detected and quantified in the positive ion mode of electrospray ionization using multiple reaction monitoring transition set at mass to charge (m/z): 347.17 ⟶ 311.12, 331.17 ⟶ 96.97, 363.11 ⟶ 121.00, 361.18 ⟶ 163.11, and 367.19 ⟶ 121.24 for 21-DOC and 17-OHP, cortisol, cortisone, and cortisol-d4 (IS), respectively. The relationship between concentration and peak area response (analyte/IS) were linear over the range of 0.25–50, 0.5–100, 1–200, and 2–400 ng/mL for 21-DOC, 17-OHP, cortisone, and cortisol, respectively. The mean extraction recovery of the analytes was in the range of 83%–96%. The coefficient of variation within and between days was less than 13.6%, and the bias ranged from −9.2% to 12%. The measured level of cortisol, cortisone, and 17-OHP was in the range of 21.9–110, 4.33–12.71, and 0.37–1.4 ng/mL, respectively. Furthermore, the measured value of cortisone–cortisol ratio was in the range of 0.08–0.21.